BBC News – creating audience in the digital era. (1st March 2016) - Fox, Andy; Mitu, Bianca
This article will examine how a public service broadcaster, specifically the BBC, delivers news content to its audience across multiple media platforms. Rather than looking at how the audience responds to media texts, this article will take the opposite standpoint by addressing the following question: How does the BBC build its audience on a platform-by-platform basis? To answer this key question we compared news outputs on the three platforms offered by the BBC: web, television and radio. A sample was compiled based on the top stories that appeared at a specific time of day over a month in early 2015. The results suggest that there is no significant difference in establishing news agendas through a digitally converged media landscape. In fact the three platforms analysed do not take media convergence into account when delivering news content.